Bovine Tuberculosis Epidemiology in Cameroon, Central Africa, Based on the Interferon-Gamma Assay - Kelly, Robert F.; Gonzaléz Gordon, Lina; Egbe, Nkongho F.; Freeman, Emily J.; Mazeri, Stella; Ngwa, Victor N.; Tanya, Vincent; Sander, Melissa; Ndip, Lucy; Muwonge, Adrian; Morgan, Kenton L.; Handel, Ian G.; et al. (Frontiers in Veterinary Science, 2022)
Despite sub-Saharan Africa (SSA) accounting for ~20% of the global cattle population, prevalence estimates and related risk factors of bovine tuberculosis (bTB) are still poorly described. The increased sensitivity of the IFN-γ assay and its practical benefits suggest the test could be useful to investigate bTB epidemiology in SSA. This study used a population-based sample to estimate bTB prevalence, identify risk factors and estimate the effective reproductive rate in Cameroonian cattle populations. A cross-sectional study was conducted in the North West Region (NWR) and the Vina Division (VIN) of Cameroon in 2013. A regional stratified sampling frame of pastoral cattle herds produced a sample of 1,448 cattle from 100 herds. In addition, a smaller cross-sectional study sampled 60 dairy cattle from 46 small-holder co-operative dairy farmers in the NWR. Collected blood samples were stimulated with bovine and avian purified protein derivatives, with extracted plasma screened using the IFN-γ enzyme-linked immunosorbent assay (Prionics Bovigam®). Design-adjusted population prevalences were estimated, and multivariable mixed-effects logistic regression models using Bayesian inference techniques identified the risk factors for IFN-γ positivity. Using the IFN-γ assay, the prevalence of bTB in the dairy cattle was 21.7% (95% CI: 11.2–32.2). The design-adjusted prevalence of bTB in cattle kept by pastoralists was 11.4% (95% CI: 7.6–17.0) in the NWR and 8.0% (95% CI: 4.7–13.0) in the VIN. A within-herd prevalence estimate for pastoralist cattle also supported that the NWR had higher prevalence herds than the VIN. Additionally, the estimates of the effective reproductive rate Rt were 1.12 for the NWR and 1.06 for the VIN, suggesting different transmission rates within regional cattle populations in Cameroon. For pastoral cattle, an increased risk of IFN-γ assay positivity was associated with being male (OR = 1.89; 95% CI:1.15–3.09), increasing herd size (OR = 1.02; 95% CI:1.01–1.03), exposure to the bovine leucosis virus (OR = 2.45; 95% CI: 1.19–4.84) and paratuberculosis (OR = 9.01; 95% CI: 4.17–20.08). Decreased odds were associated with contacts at grazing, buffalo (OR = 0.20; 95% CI: 0.03–0.97) and increased contact with other herds [1–5 herds: OR = 0.16 (95% CI: 0.04–0.55); 6+ herds: OR = 0.18 (95% CI: 0.05–0.64)]. Few studies have used the IFN-γ assay to describe bTB epidemiology in SSA. This study highlights the endemic situation of bTB in Cameroon and potential public health risks from dairy herds. Further work is needed to understand the IFN-γ assay performance, particularly in the presence of co-infections, and how this information can be used to develop control strategies in the SSA contexts.